Ectocommensal and ectoparasites in goldfish Carassius auratus (Linnaeus, 1758) in farmed in the State of São Paulo - Moyses,Carla Renata Serantoni (2015)
Concomitant infections by several parasitic genera are rare, very debilitating and often lethal to fish reared under commercial breeding conditions. Were describe a multiple and concurrent parasite infestation in cultured goldfish Carassius auratus with skin damage (nodules and/or ulceration). Fish with skin lesions underwent necropsy, and the skin and gills were scraped and examined. Histopathological examination with Hematoxylin-Eosin and Giemsa stain, and an ultrastructure study using transmission and scanning electron microscopy were conducted. In the skin, we identified multiple-parasite infestations by Gyrodactylidae, Epistylis sp., Trichodina sp., Ichthyophthirius multifiliis, Tetrahymena sp. and Ichthyobodo necator,associated with epithelial cell hyperplasia and epidermal sloughing. Although no gross lesions were observed, were identified a large number of parasites in the gills (Epistylis sp., Piscinoodinium sp., Ichthyophthirius multifiliis, Trichodina sp., Apiosoma sp., Hexamitasp. and cysts of a trematode digenean). The observed trematodes were not identified. The associated microscopic lesions were epithelial hypertrophic and hyperplasic and exhibited fusion of secondary lamellae and epithelial cell detachment. This is the first description of a protozoan Vorticella sp. parasitizing goldfish in Brazil. Multiple ectoparasitism by protozoa and Platyhelminthes, with or without apparent tissue damage, can be fatal for goldfish raised on farms with poor management.